Valoración de la Ruta "Cochahuayco-Antioquía" del Qhapaq Ñan : oportunidad de desarrollo de un turismo cultural - Sarmiento Arbieto, Stefany (2017)
The Qhapaq Ñan or Andean Road System is a network of roads built in pre-Hispanic times that served as the primary means of communication and integration among diverse populations along its path. In this section, we have chosen a segment: Cochahuayco-Antioquia for our study of sustainable use. This destination has a flow of tourists and growing expectations. However, the site has a number of constraints, all of which prevents a potential raise in the income of the district's population and interest in the care of cultural heritage. On the other hand, there is an added valued that is the rich human potential in the village, allegedly organized and interested communities. They are the tangible and intangible capital make the area suitable for a research study. The central problem is how to harness the potential of this sub-section, overcoming the limitations to generate a tourism model that is sustainable and participatory by all relevant actors. In this way, a joint private and public management will be proposed in a management plan, taking advantage the touristic potential of this Inca segment, so that it is sustainable and participatory.